Optical and structural properties of InGaN/GaN quantum well green laser diodes with AlGaN interlayer - Xuan Li; Jianping Liu; Aiqin Tian; Lei Hu; Xiaoyu Ren; Siyi Huang; Wei Zhou; Dan Wang; Deyao Li; Hui Yang (AIP Advances, 2023)
Scanning transmission electron microscope and temperature-dependent photoluminescence were used to study the effects of AlGaN interlayer (IL) following InGaN quantum wells (QWs) on the structural and optical properties of InGaN green laser diodes (LDs) grown on c-plane GaN substrate. It is found that AlGaN IL improves InGaN QW interface sharpness, whereas it does not suppress the localization effect, and moreover, it leads to increasing nonradiative recombination centers in the active region of green InGaN LD. We believe AlGaN IL has advantages and disadvantages to green InGaN LD structures. The advantage is to suppress indium (In) surface segregation, but the disadvantage is that it covers In-rich clusters, which evolve into dark spots during the growth of p-type layers of green LD structures.